The Effect of FDI on Clean Energy Consumption and CO2 Emissions: A Panel Data Analysis - Intan Karina Hapsari (JURNAL HUBUNGAN LUAR NEGERI, 2023)
The Indo-Pacific Economic Framework (IPEF) is pivotal in economic development of the Indo-Pacific region, providing a comprehensive blueprint for enhancing connectivity, trade, and investment. This research examines the third pillar of IPEF; "Clean Economy”. Foreign Direct Investment (FDI) plays a significant role in this context, influencing various economic variables. This study explores the links between FDI, clean energy consumption, and CO2 emissions, serving as proxies. Clean energy holds a critical role in the global energy transition, while CO2 emissions signify a crucial aspect of fossil fuel consumption. Progress in the IPEF negotiations, especially in Indonesia, has paved the way for potential advancements. Indonesia has actively contributed to initiatives, transforming ideas into actions. Utilizing a qualitative method and quantitative method of panel data analysis, this paper examines the correlation between FDI and the third pillar of IPEF. This paper seeks to uncover the impact of FDI on clean energy consumption and CO2 emissions, shedding light on Indonesia's role in achieving a successful transition to a clean economy.